Strategi Kreatif Film Maker Muslim dalam Mengemas Konten Dakwah Melalui Film Islami Cerita Hijrahku - Fauziah, Siti Sinta; Safei, Agus Ahmad; Sukayat, Tata (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to determine the creative strategy of Muslim Film Maker in packaging da'wah content based on the person dimension, process dimension, and press dimension through the Islamic film Cerita Hijrahku. The research method uses descriptive method, which is a method of conducting research that produces descriptive data. This study shows that in the film Cerita Hijrahku there is a concept of developing creativity in packaging da'wah content which includes 4 dimensions of creativity. First, the Person dimension in the main initiator of the production of the film Cerita Hijrahku is the producer. Second, in the process dimension Muslim Film Maker does not have a regular meeting schedule. Third, in the press dimension, Muslim Maker Films have an internal drive. Fourth, the product dimension resulting from the arrangement of creativity is in the form of a full video of the film Cerita Hijrahku.